Pengaruh Konseling Kelompok Terhadap Konformitas Siswi Kelas VIII SMPIT Bina Amal Semarang - sudyastuti, sudyastuti; mugiarso, heru (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This research was conducted based on the phenomenon that happens to grade VIII SMPIT Bina Amal Semarang which has the social conformity low. The purpose of this research is to proof  the influence of counseling service groups towards the conformity. The type of this research is experimental research. The research was conducted with seven times the grant of preferential treatment on grade VIII SMPIT Bina Amal Semarang, research subject with 8 students. The data collection method used is the psychology scale. Data analysis techniques using deskriptif analysis of percentage and wilcoxon test. The results showed incoming students conformity category is middle (59,75%). After being given the treatment through the counseling of the group, a significant unchanged in conformity of students. Conformity of the students in a middle category (60,37%). It shows that conformity of student canât be influenced through the counseling service groups. Conformity of students not depend on one cause but the another thing to establish it as cohesion,the pretension to change, and the environmental support.